2020
DOI: 10.1155/2020/4234361
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stochastically Perturbed Terminal Velocities on Convective-Scale Ensemble Forecasts of Precipitation

Abstract: The impact of stochastically perturbing the terminal velocities of hydrometeors on convective-scale ensemble forecasts of precipitation was examined. An idealized supercell storm case was first used to determine the terminal velocity error characteristics for a one-moment microphysics scheme in terms of the terminal velocities from a two-moment scheme. Two real cases were employed to evaluate the forecast skills resulting from perturbing the terminal velocities with real data. The results indicated that the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Therefore, reducing terminal velocities of graupel and hail at mid-and lower tropospheric levels would increase sources of upward-moving graupel and hail and reduce local maximum rainfall intensity. Wang [11] found that larger terminal velocity of snow and hail used in bulk microphysical schemes lead to the overestimation of precipitation intensity. Lou et al [12] found that the modified mean terminal velocity of graupel affected the collision of graupel with other hydrometeors, as well as graupel melting.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reducing terminal velocities of graupel and hail at mid-and lower tropospheric levels would increase sources of upward-moving graupel and hail and reduce local maximum rainfall intensity. Wang [11] found that larger terminal velocity of snow and hail used in bulk microphysical schemes lead to the overestimation of precipitation intensity. Lou et al [12] found that the modified mean terminal velocity of graupel affected the collision of graupel with other hydrometeors, as well as graupel melting.…”
Section: Introductionmentioning
confidence: 99%